2018
DOI: 10.1002/glia.23508
|View full text |Cite
|
Sign up to set email alerts
|

Microglia shape presynaptic properties at developing glutamatergic synapses

Abstract: Deficient neuron–microglia signaling during brain development is associated with abnormal synaptic maturation. However, the precise impact of deficient microglia function on synaptic maturation and the mechanisms involved remain poorly defined. Here we report that mice defective in neuron‐to‐microglia signaling via the fractalkine receptor (Cx3cr1 KO) show reduced microglial branching and altered motility and develop widespread deficits in glutamatergic neurotransmission. We characterized the functional proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
118
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(128 citation statements)
references
References 66 publications
8
118
2
Order By: Relevance
“…While collectively, these results demonstrate that a complementdependent synapse elimination mechanism does not target synapses in the CA1 SR of the developing hippocampus, others have found that different microglial receptors mediate synapse elimination in this region. Deletion of the fractalkine receptor CX3CR1 was found to increase the number of dendritic spines in the CA1 SR (Paolicelli et al, 2011) as well as control pre-synaptic release probability (Basilico et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While collectively, these results demonstrate that a complementdependent synapse elimination mechanism does not target synapses in the CA1 SR of the developing hippocampus, others have found that different microglial receptors mediate synapse elimination in this region. Deletion of the fractalkine receptor CX3CR1 was found to increase the number of dendritic spines in the CA1 SR (Paolicelli et al, 2011) as well as control pre-synaptic release probability (Basilico et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Microglia have recently been shown to be required for postsynaptic maturation of CA1 neurons through a CX3CR1‐dependent mechanism (Basilico et al, ). To determine whether there were also TREM2‐dependent changes in postsynaptic function in this region, we evaluated mEPSC amplitude (Figure c), mEPSC rise and decay time and AMPA:NMDA ratios, but found no significant effect of Trem2 genotype on these measures of postsynaptic function (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Complement is also involved in synaptic loss in response to acute brain injury (Alawieh, Langley, Weber, Adkins, & Tomlinson, 2018;Norris et al, 2018), chronic tau accumulation (Dejanovic et al, 2018), epilepsy (Wyatt, Witt, Barbaro, Cohen-Gadol, & Brewster, 2017), neuroinflammation (Watkins et al, 2016), and other disease contexts (Sekar et al, 2016). Other microglial signaling components also have important functions in both brain development and neurodegeneration, including CX3CR1 (Basilico et al, 2019;Paolicelli et al, 2011;Sheridan & Murphy, 2013) and progranulin (Baker et al, 2006;Lui et al, 2016), further illustrating that common mechanisms can mediate important microglial functions in brain health and disease (Tenner, Stevens, & Woodruff, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of microglia, the CNS resident immune cells and phagocytes, in synaptic refinement has been widely established. Microglial processes make direct and transient connections with subsets of neuronal synapses, with evidence for presynaptic and postsynaptic elements inside microglial lysosomes (Basilico et al, 2019;Filipello, Morini et al, 2018;Paolicelli et al, 2011;Schafer et al, 2012;Tremblay et al, 2010;Weinhard et al, 2018). Microglia-mediated synaptic pruning is a highly regulated process and occurs in several brain regions during developmental critical periods of synaptic refinement.…”
Section: Introductionmentioning
confidence: 99%